THE CONCEPT OF DEMAND AND SUPPLY IN ISLAMIC MACROECONOMICS ACCORDING TO MUHAMMAD NEJATULLAH SIDDIQI - Yusuf, Nawaf; Fatonah, Nurul Fitriani; Syamjani, Raaf; Sunengsih, Imas; Rusdiani, Meri; Rahmawati, Dessy (KOMITMEN: Jurnal Ilmiah Manajemen, 2025)
This paper is motivated by the emergence of economic problems and Islamic economic thought revived, especially after fiqh scholars and scholars in other fields of science realized that the Islamic world was lagging behind the Western world. In development, especially in modern times, fiqh scholars have a strong tendency to see various differences of opinion from various fiqh madhhabs as a unit that is not separated. Nevertheless, the difference in principles between Islamic economic figures is increasingly unstoppable in the midst of the rapid flow of the world's major ideologies, namely the economic system of Capitalism and Socialism. It is related to the emergence of economic problems, and the differences of madhhab in Islamic economic circles. Mainstream madhhab argues that overall, there is no gap between the amount of economic resources and human needs, meaning that there is a balance. This madhhab agrees that economic problems arise because of limited resources and are faced with unlimited human desires. The purpose of this paper is to understand Islamic economic thought in all its forms, to examine the concept of demand and supply of two activities that underlie economic activities, for example, the total demand and supply of rice around the world is at the equilibrium point. However, if we talk about a specific place and time, then it is very likely that there will be a scarcity of resources. This research is qualitative-research. The type of research is literature by exploring and comparing the thoughts of contemporary Islamic economic figure Muhammad Nejatullah Siddiqi. The results of this mainstream madhhab research give the most color in the discourse of Islamic economics today, so that this madhhab has no difference between conventional economics and Islamic economics. The difference is only in the mechanism for solving economic problems which according to mainstream madhhab must refer to the Qur'an and As-Sunnah.